Kinetic Separation of n‐Hexane from 2, 2‐Dimethyl Butane in Zeolite Y Using the Novel Levi–Blow Method. Issue 2 (7th December 2021) - Nag, Shubhadeep; Yashonath, Subramanian
Abstract: With stricter emission standards being implemented the world over, the increase in the research octane number (RON) is essential for continued use of fuel. This can only be achieved through the separation of the linear alkanes from the branched alkanes or through conversion of linear to branched isomer. A separation method based on levitation and blow torch effects has been recently shown to separate neopentane from n ‐pentane. The same method has been employed here to separate n ‐hexane from 2, 2‐dimethyl butane. This method provides a single step process in which the n ‐hexane can be removed completely. The method yields very high purity with minimum expenditure of energy. Several properties have been computed to quantify the separation and indicate the degree of separation. The method if implemented experimentally, will provide a generic method for the separation of molecular mixtures. The steps necessary to realize the method experimentally are discussed. The setup for scaling up of the separation using the levi–blow method for industries is also presented. Abstract : A mixture is separated through a judicious combination of levitation and blow torch effects. Red area indicates the hot zones and the potential energy landscape of the two species are indicated (see left figure). This drives the linear and branched hydrocarbons to the right and to the left respectively leading to extraordinary separation of the mixture (separation factor ≈10 16 ).